An Overview of Work-Life Integration Among Generation Z Employees - Untung, Laura Aurelia Austine; Laose, Desiana; Hindra, Aurelia; Arvaisya, Arfeina Benazir; Lie, Daniel (Psikologi Prima, 2025)
Digital transformation has brought about significant changes to the world of work, including how individuals balance their time between professional responsibilities and personal lives. The concept of Work-Life Integration (WLI) is becoming increasingly relevant, especially for Generation Z, who grew up in the digital era and have expectations of flexible work arrangements. This study aims to investigate the level of work-life integration (WLI) among Generation Z workers in Indonesia. A non-experimental, quantitative research method was employed, utilizing purposive sampling for data collection. This study used the Work-Life Limits Enactment Scale as an instrument. Data was collected through questionnaires distributed to 196 working Generation Z respondents. The results showed that the level of WLI among Generation Z fell into the low category, with a mean score of M = 3.79, which is lower than the hypothetical mean. In addition, the Work-to-Life dimension recorded a higher average score (M=4.04) compared to the Life-to-Work dimension (M=3.54). These findings suggest that Generation Z still faces challenges in integrating their work and personal lives amidst the demands of a flexible work system. This condition can be taken into consideration by companies when formulating policies aimed at improving WLI. In addition, a significant difference (t=2.00, p=0.047) was found between the level of WLI and the presence of household assistants, indicating that the level of WLI in Generation Z is higher than that of Generation Z.